Image transmission over fading channels using RS-CC versus LDPC coding - Ince, Erhan A.; Nurellari, Edmond; Iheme, Leonardo O. (My University, 2011)
In this paper we present effective means of digital image transmission by means of Forward Error Correcting (FEC) schemes and Orthogonal Frequency Division Multiplexing (OFDM). The transmission was simulated over the AWGN and a Rayleigh fading channel whose power delay profile was adopted from the ITU channel model. The FEC and OFDM parameters were adopted from the DVB-T, WiMAX, and DVB-T2 standards. The results presented herein are in terms of BER, PSNR and visual performances. It is evident from the presented results that effective FEC schemes are necessary for reliable transmission of digital media in a mobile wireless scenario.
13th International Conference on Signal and Image Processing, SIP 2011 --
Keywords: Digital Image Processing; Low-Density Parity-Check; OFDM; Rayleigh Fading Channel; Reed Solomon